Class origin, family culture, and intergenerational correlation of education in rural China - Hiroshi Sato; Shi Li (Institute for the Study of Labor (IZA), 2007)
This paper examines the determinants of intergenerational correlation of education in rural China by using a data from a large survey of households. Three generations who completed education during the period from pre-1949 to the beginning of the 2000s are included. The focus is on the influence of family class status (chengfen) on offspring education. Our investigation suggests that family class status is still important for the intergenerational transmission of education. The offspring of landlord/rich peasant families are more likely to achieve higher educational attainment, even though parental education, family wealth, and other family characteristics are the same. The unique determinant of the intergenerational transmission of education in the postreform era is found to be an education-oriented family culture, created as an intergenerational cultural rebound against class-based social discrimination during the Maoist era. We have also found that the cultural reaction is a combination of class-specific effects with cohort-specific effects
urn:nbn:de:101:1-20080416205
Keywords: 330; Bildungsniveau; Generationenbeziehungen; Soziale Schicht; Familiensoziologie; Ländlicher Raum; China